КИЧИК МАКТАБ ЁШИДАГИ ЎҚУВЧИЛАРНИНГ ПСИХОЛОГИК ХУСУСИЯТЛАРИ - Қурбамуратова, З. (SCIENCE and SOCIETY, 2017)
The article raises the problems of creating conditions for the mental perception, sensitivity, observation, memory of younger schoolchildren in the course of training. The author also paid attention to the formation of students’ skills such as reading, writing, counting, which depends on the level of perception and which will become the prospective duties in future.
Keywords: influence of education; anatomical and physiological characteristics; the level of psychological development; physical development; conversation; age and psychological characteristics; confidence and personality of the teacher; the theoretical knowledge; practical knowledge; involuntary attention; voluntary attention; verbal and logical memory; perception